A system for EPID‐based real‐time treatment delivery verification during dynamic IMRT treatment. Issue 9 (9th August 2013) - Fuangrod, Todsaporn; Woodruff, Henry C.; van Uytven, Eric; McCurdy, Boyd M. C.; Kuncic, Zdenka; O'Connor, Daryl J.; Greer, Peter B.
Abstract : Purpose: : To design and develop a real‐time electronic portal imaging device (EPID)‐based delivery verification system for dynamic intensity modulated radiation therapy (IMRT) which enables detection of gross treatment delivery errors before delivery of substantial radiation to the patient. Methods: : The system utilizes a comprehensive physics‐based model to generate a series of predicted transit EPID image frames as a reference dataset and compares these to measured EPID frames acquired during treatment. The two datasets are using MLC aperture comparison and cumulative signal checking techniques. The system operation in real‐time was simulated offline using previously acquired images for 19 IMRT patient deliveries with both frame‐by‐frame comparison and cumulative frame comparison. Simulated error case studies were used to demonstrate the system sensitivity and performance. Results: : The accuracy of the synchronization method was shown to agree within two control points which corresponds to approximately ∼1% of the total MU to be delivered for dynamic IMRT. The system achieved mean real‐time gamma results for frame‐by‐frame analysis of 86.6% and 89.0% for 3%, 3 mm and 4%, 4 mm criteria, respectively, and 97.9% and 98.6% for cumulative gamma analysis. The system can detect a 10% MU error using 3%, 3 mm criteria within approximately 10 s. The EPID‐based real‐time delivery verification system successfully detected simulated gross errors introduced into patient plan deliveries in near real‐time (within 0.1 s). Conclusions: : A real‐time radiation delivery verification system for dynamic IMRT has been demonstrated that is designed to prevent major mistreatments in modern radiation therapy.